A phase 1 study of the Janus kinase 2 (JAK2)V617F inhibitor, gandotinib (LY2784544), in patients with primary myelofibrosis, polycythemia vera, and essential thrombocythemia - Verstovsek, Srdan; Mesa, Ruben A.; Salama, Mohamed E.; Li, Li; Pitou, Celine; Nunes, Fabio P.; Price, Gregory L.; Giles, Jennifer L.; D’Souza, Deborah N.; Walgren, Richard A.; Prchal, Josef T. (Leukemia research, 2017)
•Gandotinib shows increased potency for the JAK2V617F mutation.•The recommended phase 2 dose of 120mg was associated with clinical improvement.•Findings at the maximum-tolerated dose of 120mg supported further clinical testing.•Gandotinib demonstrated an acceptable safety and tolerability profile. Mutations in Janus kinase 2 (JAK2) are implicated in the pathogenesis of Philadelphia-chromosome negative myeloproliferative neoplasms, including primary myelofibrosis, polycythemia vera, and essential thrombocythemia. Gandotinib (LY2784544), a potent inhibitor of JAK2 activity, shows increased potency for the JAK2V617F mutation. The study had a standard 3+3 dose-escalation design to define the maximum-tolerated dose. Primary objectives were to determine safety, tolerability, and recommended oral daily dose of gandotinib for patients with JAK2V617F-positive myelofibrosis, essential thrombocythemia, or polycythemia vera. Secondary objectives included estimating pharmacokinetic parameters and documenting evidence of efficacy by measuring clinical improvement. Thirty-eight patients were enrolled and treated (31 myelofibrosis, 6 polycythemia vera, 1 essential thrombocythemia). The maximum-tolerated dose of gandotinib was 120mg daily, based on dose-limiting toxicities of blood creatinine increase or hyperuricemia at higher doses. Maximum plasma concentration was reached 4h after single and multiple doses, and mean half-life on day 1 was approximately 6h. Most common treatment-emergent adverse events were diarrhea (55.3%) and nausea (42.1%), a majority of which were of grade 1 severity. Best response of clinical improvement was achieved by 29% of myelofibrosis patients. A ≥50% palpable spleen length reduction was observed at any time during therapy in 20/32 evaluable patients. Additionally, ≥50% reduction in the Total Symptom Myeloproliferative Neoplasm Symptom Assessment Form Score was seen in 11/21 (52%) and 6/14 patients (43%) receiving ≥120mg at 12 and 24 weeks respectively. Gandotinib demonstrated an acceptable safety and tolerability profile, and findings at the maximum-tolerated dose of 120mg supported further clinical testing. Clinicaltrials.gov identifier: NCT01134120.